Diversifying agriculture in post-conflict areas: 7 things we can change - Ekesa, Beatrice; Baganizi, Mary; Dolan, Ian (2020)
Agricultural biodiversity is central to current and future food and nutrition and security needs in Uganda. Unfortunately, in some parts of the country, such as Teso and Acholi sub regions, which faced up to two decades of conflict, this diversity is increasingly under threat from practices such as charcoal making and land clearing for agriculture. As a result, there is reduced investment in longer term sustainable farming practices that conserve and promote diversity. This contributes to high food insecurity and lack of access to diverse diets especially among vulnerable groups such as Women of Reproductive Age (WRA) (15-49 years) and children under five years. Adoption of sustainable agricultural practices can promote agrobiodiversity and enhance nutritional outcomes and quality of life of vulnerable groups. This brief gives a summary of findings and insights from research conducted in 2018 by Bioversity International and Trocaire, Uganda, working closely with a number of partners including National Agriculture Research Organisation (NARO), Makerere University and Ministry of Health-Uganda (Division of Nutrition). It points out interventions and actions that can be implemented in culturally.